A Comparative Analysis of Students' Understanding in Social Studies: Unraveling the Nuances of Online and Offline Learning: Analisis Perbandingan Pemahaman Siswa dalam Studi Sosial: Mengungkap Nuansa Pembelajaran Daring dan Tatap Muka - Zahrah , Tsalasah Alfirdausi; Rezania, Vanda (Universitas Muhammadiyah Sidoarjo, 2023)
This research examines the disparity in students' comprehension of social studies materials during online and offline learning for Class IV SDN Pagerwojo. Employing a non-experimental quantitative ex post facto method, documentation of value data collection was employed as the instrument. The results indicate that online learning yields a mean understanding score of 70 (medium category) with a standard deviation of 10, while offline learning achieves a mean score of 73 (moderate category) with a standard deviation of 13. The findings suggest a discernible variance in students' understanding between the two modes of learning, albeit not significantly pronounced. The implications of this study contribute to the ongoing discourse on optimizing learning environments to better support students' comprehension in social studies subjects. Highlights: Insightful Comparison: This research delves into a comparative analysis of students' understanding of social studies materials in both online and offline learning environments, shedding light on the nuanced differences between the two. Moderate Disparity: The study reveals a moderate variance in students' comprehension levels between online and offline learning, emphasizing the need for further exploration to optimize educational approaches. Implications for Education: The findings have significant implications for educators, highlighting the importance of tailoring teaching strategies to maximize students' understanding of social studies subjects across different learning platforms. Keywords: Students' Understanding, Social Studies, Online Learning, Offline Learning, Comparative Analysis